Neural correlates of deception in social contexts in normally developing children - Yokota, Susumu; Taki, Yasuyuki; Hashizume, Hiroshi; Sassa, Yuko; Thyreau, Benjamin; Tanaka, Mari; Kawashima, Ryuta (Frontiers in Human Neuroscience, 2013)
Deception is related to the ability to inhibit prepotent responses and to engage in mental tasks such as anticipating responses and inferring what another person knows, especially in social contexts. However, the neural correlates of deception processing, which requires mentalizing, remain unclear. Using functional magnetic resonance imaging (fMRI), we examined the neural correlates of deception, including mentalization, in social contexts in normally developing children. Healthy right-handed children (aged 8–9 years) were scanned while performing interactive games involving deception. The games varied along two dimensions: the type of reply (deception and truth) and the type of context (social and less social). Participants were instructed to deceive a witch and to tell the truth to a girl. Under the social-context conditions, participants were asked to consider what they inferred about protagonists’ preferences from their facial expressions when responding to questions. Under the less-social-context conditions, participants did not need to consider others’ preferences. We found a significantly greater response in the right precuneus under the social-context than under less-social-context conditions. Additionally, we found substantially greater activation in the right inferior parietal lobule (IPL) under the deception than under the truth condition. These results suggest that deception in a social context requires not only inhibition of prepotent responses but also engagement in mentalizing processes. This study provides the first evidence of the neural correlates of the mentalizing processes involved in deception in normally developing children.